Anoctamin 9/TMEM16J is a cation channel activated by cAMP/PKA signal - Kim, Hyungsup; Kim, Hyesu; Lee, Jesun; Lee, Byeongjun; Kim, Hee-Ryang; Jung, Jooyoung; Lee, Mi-Ock; Oh, Uhtaek (ELSEVIER SCI LTD, 2018)
Anoctamins (ANOs) are multifunctional membrane proteins that consist of 10 homologs. ANO1 (TMEM16A) and ANO2 (TMEM16B) are anion channels activated by intracellular calcium that meditate numerous physiological functions. ANO6 is a scramblase that redistributes phospholipids across the cell membrane. The other homologs are not well characterized. We found ANO9/TMEM16J is a cation channel activated by a cAMP-dependent protein kinase A (PKA). Intracellular cAMP-activated robust currents in whole cells expressing ANO9, which were inhibited by a PKA blocker. A cholera toxin that persistently stimulated adenylate cyclase activated ANO9 as did the application of PKA. The cAMP-induced ANO9 currents were permeable to cations. The cAMP-dependent ANO9 currents were augmented by intracellular Ca-2+. Ano9 transcripts were predominant in the intestines. Human intestinal SW480 cells expressed high levels of Ano9 transcripts and showed PKA inhibitor-reversible cAMP-dependent currents. We conclude that ANO9 is a cation channel activated by a cAMP/PKA pathway and could play a role in intestine function.
Keywords: CA2+-ACTIVATED CL-CHANNEL; CHLORIDE CHANNEL; THERAPEUTIC TARGET; INTERSTITIAL-CELLS; 1 TMEM16A; EXPRESSION; TUMORIGENESIS; MUTATIONS; SECRETION; CURRENTS